Radiation tolerance of the LHCb outer tracker: in the lab and in the forward region at the LHC - Tuning, Niels; Bachmann, Sebastian; Pellegrino, Antonio; Uwer, Ulrich; Wiedner, Dirk (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2025)
During the detector construction phase between 2004 and 2006, it was discovered that the LHCb Outer Tracker (OT) detector suffered from gain loss after irradiation in the laboratory at moderate intensities. Under irradiation an insulating layer was formed on the anode wire. The aging was caused by contamination of the counting gas due to outgassing of the glue used in construction namely araldite AY103-1. The gain loss was concentrated upstream the gas flow, and at moderate irradiation intensity only. The aging rate was reduced by longterm flushing and by the addition of a few percent of O2 to the gas mixture. Furthermore, applying a large positive high voltage (beyond the amplification regime) has shown to remove the insulating deposits without damaging the wire surface. This paper presents the history of the developments together with the characteristics and the culprit of the aging phenomenon and the resulting detector performance in situ.
Gesehen am 02.10.2025